The impact of musical fit and sound design on consumers' perception of a luxury car ad - Sze Yeoh, Joanne Pei; Han, Min Gin; Spence, Charles (Taylor and Francis Group, 2023)
A study is reported that was designed to investigate the influence of various kinds of sonic accompaniment on consumers’ perception of a high-end luxury sports car. Using a between-participants experimental design, groups of 40 participants viewed a short car ad. The groups heard either classical music, pop music, sound effects, or listened in silence. The results revealed that participants perceived the car’s power, driving excitement and engine technology to be highest when the ad was paired with sound effects. Meanwhile, participants perceived the car to be most elegant and indicated the highest price for the car when the ad was paired with classical music. Those participants who watched the ad in silence rated lowest for all aspects of the car’s characteristics, including indicating the lowest price for the car. Interestingly, the participants admitted that music/sound effects influenced their perception of the advertised luxury sports car. This implies that specially curated sound design may help to highlight specific characteristics of a car.